Roles Played by the PI3K/Akt/HIF-1α Pathway and IL-17A in the Chinese Subtype of Chronic Sinusitis with Nasal Polyps - Cheng, Ke-Jia; Zhou, Min-Li; Liu, Yong-Cai; Zhou, Shui-Hong (Mediators of Inflammation, 2022)
Background. The Chinese subtype of CRSwNP may have a unique pathogenesis. This study was designed to seek the role of the PI3K/Akt/HIF-1α pathway and IL-17A in CRSwNP. Methods. The total IgE, ECP, and IL-17A levels were determined by UniCAP100 and ELISA. The activity of MPO was detected by the biochemical techniques. The protein expressions of HIF-1α, p-Akt, and PI3K were detected by the WB method. HIF-1α and IL-17A mRNA levels were measured by RT-PCR. Results. The CRSwNP group showed significantly elevated MPO activity, PI3K, p-AKT protein, HIF-1α, and IL-17A mRNA levels in nasal polyps. Stimulated by the TNF-α, the PI3K, p-AKT, HIF-1α, and IL-17A levels significantly elevated in the fibroblasts. Inhibited by the Wortmannin, those indicators significantly declined in the fibroblasts. Conclusion. The PI3K/Akt/HIF-1α pathway played a role in the pathogenesis of CRSwNP. The elevated IL-17A level might be responsible for the neutrophilic inflammation in CRSwNP. The PI3K/Akt/HIF-1α pathway might regulate the IL-17A-related inflammation in CRSwNP.